DECISION SUPPORT SYSTEM FOR SCHOLARSHIP ADMISSION USING SIMPLE ADDITIVE WEIGHTING (SAW) METHOD - Martin, Afrizal; Andoyo, Andreas; Widiyanto, Widiyanto (Universitas Islam Negeri Raden Intan Lampung, 2024)
Implementing the scholarship recipient selection process funded by the government is aimed at ensuring students receive adequate education and avoid dropping out of school. This scholarship serves as assistance to help students complete their educational tasks in seeking knowledge until the scholarship period ends, in the form of financial aid to support the expenses incurred by students during their educational journey. However, the selection process requires a long time to ensure that the aid recipients are truly deserving students. To assist in determining eligible scholarship recipients, a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method is needed. SAW is a simple ranking method that calculates weighted values based on criteria. With the implementation of the SAW-based decision support system for scholarship selection, the final result obtained from the summation yields A1 as the best alternative for scholarship recipients.